The Influence of Facilities and Individual Interests on Students' Interest in the Educational Administration Study Program at State Vocational High School 1 Stabat - Rizki, Ananda; Faqrurrowzi, Lendra; Damanik, Rabukit (LPPM Institut Pendidikan Nusantara Global, 2025)
Education plays a vital role in shaping an individual’s future, serving as a key foundation to face global challenges and improve quality of life. After completing secondary education, students are expected to choose a college major that aligns with their interests and abilities. This study aims to analyze the factors influencing the interest of grade XII students at State Vocational High School 1 Stabat in selecting the Educational Administration Study Program. This research employs a descriptive quantitative approach, with a sample of 36 students selected using stratified random sampling techniques. Data were collected through questionnaires. The results of the chi-square test revealed that the availability of facilities (p = 0.04), parents’ socioeconomic status (p = 0.01), motivation from family and friends (p = 0.02), and individual interests (p = 0.00) significantly influenced students’ interest in choosing the study program (p < 0.05). These findings suggest that environmental, social, and personal factors play a crucial role in educational decision-making. Therefore, it is recommended that students, particularly those in their final year, become more proactive in seeking information about potential study programs by considering environmental support and self-potential, so that the decisions made are more accurate and aligned with their interests.